İnflammatory pseudotumor of the liver: clinical and pathological features of two patients - Semin AYHAN; Funda YILMAZ; Gül YÜCE; Yıldıray YÜZER; Ahmet MEMİŞ and Ali MENTEŞ (Turkish Journal of Gastroenterology, 2019)
-